Scaling the Computer to the Problem: Application Programming with Unlimited Memory. - Nassi, Ike (Computer (00189162), 2017)
Instead of scaling an application and data around the computer, programmers can use a software-defined server—an inverse hypervisor—in which multiple physical machines run a single virtual machine. Memory can be expanded as needed without modifying the application or limiting its data.